Scale effect research on cavity evolution and impact load characteristics during high-speed water entry - Yao Shi; Peiqi Che; Qiaogao Huang; Guang Pan (Ocean Engineering, 2026)

Drought-rehydration enhances yield through optimized soil multifunctionality in drip-irrigated spring wheat in arid regions - Rongrong Wang; Guang Shi; Shuting Bie; Ziqiang Che; Yiling Ma; Guiying Jiang; Jianguo Liu (Soil and Tillage Research, 2026)

A wheat seedling detection model based on efficient feature extraction and coordinate attention mechanism - Shun Wang; Bowen Zhang; Yinchao Che; Guang Zheng; Yanna Ren; Lei Xi; Xinming Ma; Shuping Xiong (European Journal of Agronomy, 2026)

Research progress on performance regulation strategies for copper-based nitrate reduction catalysts for ammonia synthesis - Yuru Song; Tan Zhang; Zhikai Che; Jinping Li; Guang Liu (Chemical Engineering Journal, 2026)

Mechanosensor YAP orchestrates human neural rosette morphogenesis via TEAD4-LEF1 transcriptional nexus - Jinghao Hu; Zan He; Huifang Hu; Xiaoyan Sun; Shanshan Che; Shuhui Sun; Miyang Ma; Yixin Zhang; Shuai Ma; Weiqi Zhang; Juan Carlos Izpisua Belmonte; Guoguang Zhao; et al. (Science China Life Sciences, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

A new generation aerosol optical depth dataset based on AVHRR data over China from 1981 to 2000 - Yahui Che; Jie Guang; Yong Xue; Gerrit de Leeuw; Lu She; Linlu Mei; Xingwei He; Ling Sun; Zhengqiang Li (Remote Sensing of Environment, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

Synergistic effect of holey graphene and CoSe2-NiSe2 heterostructure to enhance fast Na-ion transport - Chong Xu; Kaiyi Chen; Jiahao Yang; Guang Ma; Ye Wang; Zizheng Zhou; Zhixuan Wu; Sai Che; Zechen Li; Yuxin Tu; Zhihua Xiao; Daqiang Jiang; et al. (Chemical Engineering Journal, 2024)

CoSe2-Modified multidimensional porous carbon frameworks as high-Performance anode for fast-Charging sodium-Ion batteries - Chong Xu; Jiahao Yang; Kaiyi Chen; Guang Ma; Ye Wang; Zechen Li; Zizheng Zhou; Zhixuan Wu; Sai Che; Changsheng Ding; Yongfeng Li (Chemical Engineering Journal, 2024)

Study on the cavity evolution and load characteristics of large projectile during high-speed water entry - Peiqi Che; Yao Shi; Hairui Zhao; Yilan Yu; Guang Pan (Ocean Engineering, 2024)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

The bioconcentration ability of heavy metal research for 50 kinds of rice under the same test conditions - Wen-Juan Xie; Lei Che; Guang-Yu Zhou; Li-Na Yang; Min-Yu Hu (Environmental Monitoring and Assessment, 2016)

Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae) - Peng Guo; Qin Liu; Fei Zhu; Guang H. Zhong; Xin Chen; Edward A. Myers; Jing Che; Liang Zhang; Thomas Ziegler; Truong Q. Nguyen; Frank T. Burbrink (Molecular Ecology, 2016)
Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mt DNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.

VPA inhibits renal cancer cell migration by targeting HDAC2 and down-regulating HIF-1α - Feng-qiang Yang; Min Liu; Feng-ping Yang; Jianping Che; Wei Li; Wei Zhai; Guang-chun Wang; Jun-hua Zheng; Xi Li (Molecular Biology Reports, 2014)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

D-RNA Molecules Associated with Subisolates of the VT Strain of Citrus Tristeza Virus which Induce Different Seedling-Yellows Reactions - Guang Yang; Xibing Che; Rose Gofman; Yossi Ben-Shalom; Dan Piestun; Ron Gafny; Munir Mawassi; Moshe Bar-Joseph (Virus Genes, 1999)